PENGARUH PENGGUNAAN MEDIA ANIMASI TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA PEMBELAJARAN IPAS KELAS IV SD NEGERI 124385 PEMATANGSIANTAR - Nurintan Hutapea; Aprido Bernando Simamora; Muktar Panjaitan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The low level of students’ creative thinking skills in elementary IPAS learning, as indicated by low learning achievement and the dominance of conventional teaching methods, forms the background of this study. This study aims to determine the effect of using animation media on the creative thinking skills of fourth-grade students at SD Negeri 124385 Pematangsiantar. This research employed a quantitative approach with an experimental method using a one-group pretest-posttest design. The subjects of this study were 28 students. Data were collected through essay tests measuring indicators of creative thinking, including fluency, flexibility, elaboration, and originality. Data analysis techniques included normality testing, t-test, and N-Gain analysis. The results showed an improvement in students’ creative thinking skills after the implementation of animation media, as evidenced by the difference between pretest and posttest scores and the N-Gain results categorized as improvement. Therefore, it can be concluded that the use of animation media has a significant effect on students’ creative thinking skills in IPAS learning.